Old aviances ; Iodine deficiency ; Spyro-Gyra [videorecording] - Lazaro, Cheche (The Probe Team ; [episode no. 167], 1991)
Rejection of the twelve senate committee on the American military bases and the relation between the Philippines and the United States; Goiter problem on the women of Cordillera due to lack of iodine; A jazz group named Spyro Gyra whose music were purely jazz.